Prospects for Renovation of Prefabricated Buildings as a Source of Redevelopment without the Demolition of Existing Buildings - KOZHEVNIKOV, Dmitry (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
The paper defines the conditions, methods and forms of the renovation of the buildings in cases when they do not require a significant investment and new construction at forming of the structure of construction system. It is shown that the use of buildings for renovation without their demolition and repeated construction, has been tested to a large extent not only in the territory of the countries where commercial housing construction has been largely used in a long exposure, but also in the countries of former ‘Socialist bloc’. Countries, where panel housing construction accounts for more than 30% of the entire house fund and gradually leads to its destruction due the end of life, were taken as the examples. The novelty of the paper is the position offering not only the housing renovation measures, but also the design solutions that may be used in the development of the overall concept of house-building strategy. The article has its applied value in the structure of development of integral video-ecological bases for the design of mass buildings of housing construction. The further direction of research is determining of the possible development of panel housing construction in the territory of the state, due to the extensive experience in the construction of similar buildings of the housing stock.